Gaia white dwarfs within 40 pc - III. Spectroscopic observations of new candidates in the Southern hemisphere - O'Brian, Mairi; Tremblay, Pier-Emmanuel; Gentile Fusillo, N P; Hollands, M. A.; Gänsicke, B. T.; Koester, D.; Pelisoli, I.; Cukanovaite, E.; Cunningham, T.; Doyle, A. E.; Elms, A.; Farihi, J.; et al. (Monthly notices of the Royal Astronomical Society, 2023)
We present a spectroscopic survey of 248 white dwarf candidates within 40 pc of the Sun; of these 244 are in the Southern hemisphere. Observations were performed mostly with the Very Large Telescope (X-Shooter) and Southern Astrophysical Research Telescope. Almost all candidates were selected from Gaia Data Release 3 (DR3). We find a total of 246 confirmed white dwarfs, 209 of which had no previously published spectra, and two main-sequence star contaminants. Of these, 100 white dwarfs display hydrogen Balmer lines, 69 have featureless spectra, and two show only neutral helium lines. Additionally, 14 white dwarfs display traces of carbon, while 37 have traces of other elements that are heavier than helium. We observe 35 magnetic white dwarfs through the detection of Zeeman splitting of their hydrogen Balmer or metal spectral lines. High spectroscopic completeness (> 97 per cent) has now been reached, such that we have 1058 confirmed Gaia DR3 white dwarfs out of 1083 candidates within 40 pc of the Sun at all declinations.
Gesehen am 25.01.2024